The obstacles that limit the performance of the university professor in the requirements of the quality of higher education - Boussag, Hadjira; Bounif, Hanane (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The professor is considered as one of the most important parts of higher education. He has many roles and tasks which contribute in the success of university educational process to get the desired results. University is considered as a system which forms the social reality. It makes thought leaders, the source of knowledge who form the national culture. It cannot play this great role unless there were available material and human capabilities to overcome the obstacles which professor may face. Although we believe that professor effectiveness be influenced by the social reality but university as a sub-system of systems which forms the social reality is one of the internal causes which make a source of many obstacles that impede the professor to do his role in the right way. An analytical descriptive approach was applied in this study. The purpose of the present study is to identify the obstacles inside and outside university by relying on two sub-hypotheses, each hypothesis contains verified indicators. In our results we find that there are obstacles inside and outside university which impede professor performance and as a final step we reached a set of suggestions.